(untitled) (Research, Society and Development, 2021)
Tuberculosis (TB) is an infectious and endemic infectious disease, caused by Mycobacterium tuberculosis, reaching almost all organs and tissues of the human body. This study aimed to describe the epidemiological aspects of tuberculosis in the city of Caxias in the state of Maranhão in the period 2015-2019. This is a documentary, descriptive, retrospective study, with a quantitative approach to the data, carried out from 2015 to 2019, using data from the Ministry of Health’s Notifiable Diseases Information System (SINAN). This study evaluated 325 cases of TB in the mentioned period. It can be observed that there was a prevalence of TB cases in males (67.7%), in which there was a predominance of the age group of 20 to 39 years (33.5%). Regarding race, there was a statistically significant prevalence of brown skin (70.8%), in which most individuals had low education. With regard to prevalence, 2016 had the highest rates (23.7%). The predominant clinical form of the disease was pulmonary (91.4%), in which almost all were new cases (82.8%). In view of the problems encountered, it is clear that TB remains a major public health problem. It is necessary that more actions aimed at combating pathology be put into practice and that governments see the extent of the problem. It is considered that more studies should be carried out in this line of investigation, in order to prove the need to search for new ways to approach the theme, aiming to decrease the number of cases.